Microbial dynamics and soil physicochemical properties explain large‐scale variations in soil organic carbon. (12th February 2020) - Zhang, Haicheng; Goll, Daniel S.; Wang, Ying‐Ping; Ciais, Philippe; Wieder, William R.; Abramoff, Rose; Huang, Yuanyuan; Guenet, Bertrand; Prescher, Anne‐Katrin; Viscarra Rossel, Raphael A.; Barré, Pierre; Chenu, Claire; et al.
Abstract: First‐order organic matter decomposition models are used within most Earth System Models (ESMs) to project future global carbon cycling; these models have been criticized for not accurately representing mechanisms of soil organic carbon (SOC) stabilization and SOC response to climate change. New soil biogeochemical models have been developed, but their evaluation is limited to observations from laboratory incubations or few field experiments. Given the global scope of ESMs, a comprehensive evaluation of such models is essential using in situ observations of a wide range of SOC stocks over large spatial scales before their introduction to ESMs. In this study, we collected a set of in situ observations of SOC, litterfall and soil properties from 206 sites covering different forest and soil types in Europe and China. These data were used to calibrate the model MIMICS (The MIcrobial‐MIneral Carbon Stabilization model), which we compared to the widely used first‐order model CENTURY. We show that, compared to CENTURY, MIMICS more accurately estimates forest SOC concentrations and the sensitivities of SOC to variation in soil temperature, clay content and litter input. The ratios of microbial biomass to total SOC predicted by MIMICS agree well with independent observations from globally distributed forest sites. By testing different hypotheses regarding (using alternative process representations) the physicochemical constraints on SOC deprotection and microbial turnover in MIMICS, the errors of simulated SOC concentrations across sites were further decreased. We show that MIMICS can resolve the dominant mechanisms of SOC decomposition and stabilization and that it can be a reliable tool for predictions of terrestrial SOC dynamics under future climate change. It also allows us to evaluate at large scale the rapidly evolving understanding of SOC formation and stabilization based on laboratory and limited filed observation. Abstract : Microbial explicit decomposition models have been developed to replace the conventional first‐order model used in most Earth System Models, but their evaluation was limited to observations from laboratory incubations or few field experiments. A comprehensive evaluation of these models is essential using large‐scale in situ observations. We found that, compared to first‐order decomposition model, microbial explicit model more accurately estimates SOC concentrations, microbe/SOC ratio, SOC composition and the sensitivities of SOC stock to changed climate, litter input and soil properties. We support to replace the first‐order decomposition model used in existing Earth System Models with microbial explicit model.